2009
DOI: 10.1179/102453309x446144
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient consolidation chemotherapy in pediatric acute myeloid leukemia: a retrospective analysis

Abstract: Outpatient AML consolidation therapy is safe and feasible in children. It appears to result in less frequent invasive blood studies; shorter duration of febrile neutropenia and consequently less antimicrobial and antifungal usage as compared to inpatient consolidation cycles. To our knowledge, this report is the first of its kind looking specifically at outpatient consolidation chemotherapy in AML.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…were the most common gram positive organisms. The rate of CNST isolates was not statistically different between C1 and C2, however, Streptococcus isolates, particularly S. viridans, increased from C1 to C2 within the younger cohort, likely reflecting the cumulative effects of HiDAC chemotherapy [11,28,30-32]. …”
Section: Discussionmentioning
confidence: 98%
“…were the most common gram positive organisms. The rate of CNST isolates was not statistically different between C1 and C2, however, Streptococcus isolates, particularly S. viridans, increased from C1 to C2 within the younger cohort, likely reflecting the cumulative effects of HiDAC chemotherapy [11,28,30-32]. …”
Section: Discussionmentioning
confidence: 98%
“…It is also associated with significant financial burden for the family especially in resource poor settings [6]. There is paucity of published data from India on pediatric AML, treatment protocol and cytogenetics based risk stratification.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this study represents the largest series of ambulatory AML consolidation patients reported to date and, unlike previous studies [1][2][3][4][5][6][7], includes a large proportion of patients over age 60. Overall, 50% of letters patients required readmission, mostly for treatment of febrile neutropenia with a mean duration of readmission of 2 weeks; therefore, even patients requiring readmission spent considerably less time as inpatients than would have been expected if they had been managed entirely on an inpatient basis.…”
Section: Patient Characteristics Are Shown Inmentioning
confidence: 99%
“…Intensive consolidation chemotherapy for acute myeloid leukemia (AML) patients in complete remission is being increasingly administered on an outpatient basis. Although this approach has been found to be safe and feasible in younger patients [1][2][3][4][5][6], its safety in older patients remains unknown. We therefore undertook an evaluation of outpatient-based consolidation chemotherapy in older AML patients, and compared results to younger patients treated at the same institution over the same time period.…”
mentioning
confidence: 99%
See 1 more Smart Citation